Stress-strain relationship of steel fiber reinforced fully recycled coarse/fine aggregate concrete under cyclic loading - Shuqi Guo; Yahong Ding; Ping Xu; Jun Wu; Jiuwen Bao (Case Studies in Construction Materials)
This study examines the stress-strain behavior of recycled concrete subjected to various recycled material mixture systems and varying steel fiber (SF) volume contents. Uniaxial cyclic loading tests were conducted to assess the failure modes, stress-strain curves, axial compressive strength, and residual strains. The findings indicate that incorporating recycled materials shift the failure mode from vertical splitting to oblique shear and reduces the stress-strain curve's ascending slopes and axial compressive strength. Specifically, the strength of fully recycled aggregate concrete experienced the greatest reduction of 26.27 % relative to natural concrete, and only a 2.4 % reduction compared to fully recycled fine aggregate concrete (FRFAC). The inclusion of SF significantly enhances the cyclic compression resistance and ductility of recycled concrete, increasing both the cycle count and the maximum cumulative residual strain. At a fiber content of 1.5 %, FRFAC's cycle count increased by 20 compared to the control, and the maximum cumulative residual strain rose from 0.86 to 10.38. The relationship between residual strain and unloaded/reloaded strain is described by introducing recycled material coefficient and SF characteristic parameter. Based on the test data, the unloading and reloading equations proposed, and the damage evolution equation including residual strain proposed on the basis of stiffness degradation. A constitutive model for SF reinforced fully recycled coarse/fine aggregate concrete is developed, capable of characterizing the effects of different recycled materials and SF content. This model accurately predicts the unloading/reloading path, residual strain progression, and damage evolution.